Exploring the diversity of Type 1 active galactic nuclei identified in SDSS-IV/SPIDERS. Issue 3 (8th January 2020) - Wolf, Julien; Salvato, Mara; Coffey, Damien; Merloni, Andrea; Buchner, Johannes; Arcodia, Riccardo; Baron, Dalya; Carrera, Francisco J; Comparat, Johan; Schneider, Donald P; Nandra, Kirpal
ABSTRACT: We present a statistical analysis of the optical properties of an X-ray-selected Type 1 active galactic nucleus (AGN) sample, using high signal-to-noise ratio (S/N>20) spectra of the counterparts of the ROSAT /2RXS sources in the footprint of the SDSS-IV/SPIDERS (Spectroscopic IDentification of eROSITA Sources) programme. The final sample contains 2100 sources. It significantly extends the redshift and luminosity ranges ( z ∼ 0.01–0.80 and L_0.1\!-\!2.4 keV 2.0 × 10^41\!-\!1.0 × 10^46 erg s^-1 ) used so far in this kind of analysis. By means of a principal component analysis, we derive eigenvector (EV) 1 and 2 in an eleven-dimensional optical and X-ray parameter space, which are consistent with previous results. The validity of the correlations of the Eddington ratio L/L Edd with EV1 and the black hole mass with EV2 is strongly confirmed. These results imply that L/L Edd and black hole mass are related to the diversity of the optical properties of Type 1 AGNs. Investigating the relation of the width and asymmetry of H β and the relative strength of the iron emission r_Fe II, we show that our analysis supports the presence of a distinct kinematic region: the very broad line region. Furthermore, comparing sources with a red-asymmetric broad H β emission line to sources for which it is blue asymmetric, we find an intriguing difference in the correlation of the Fe II and the continuum emission strengths. We show that this contrasting behaviour is consistent with a flattened, stratified model of the broad-line region, in which the Fe II -emitting region is shielded from the central source.